The Cancer Principle-I: Introducing Cancer as a Fundamental Principle of Nature (Indian Journal of Public Health Research & Development, 2020)
In a series of five articles we put forth and establish a new principle, namely the cancer principle which wepropose as a fundamental principle of nature. Cancer is an agent of the principle of disorder and is at theroot of origin of life, evolution of species and may be, is also the determinant of the ultimate fate of all life.We introduce and motivate this principle and provide arguments in favor of its being at the origin of allevolution. Cancer is defined as the tendency for unrestrained proliferation that is operative in both inanimateand animate worlds and that has given rise to the phenomenon of life from the nonliving background.
Keywords: cancer, disorder, order, evolution, self-replication